2007
DOI: 10.1096/fj.06-7986com
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular chaperone clusterin influences amyloid formation and toxicity by interacting with prefibrillar structures

Abstract: Clusterin is an extracellular chaperone present in all disease-associated extracellular amyloid deposits, but its roles in amyloid formation and protein deposition in vivo are poorly understood. The current study initially aimed to characterize the effects of clusterin on amyloid formation in vitro by a panel of eight protein substrates. Two of the substrates (Alzheimer's beta peptide and a PI3-SH3 domain) were then used in further experiments to examine the effects of clusterin on amyloid cytotoxicity and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
295
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 283 publications
(323 citation statements)
references
References 36 publications
24
295
1
3
Order By: Relevance
“…We observed that both species reduced very significantly the degree of Ca 2+ influx while incubation with an anti ‐GFP antibody, as a control that does not bind to the Aβ peptide, had no detectable effect. These results are consistent with previous reports that clusterin30, 31 and Nb3 bind to oligomers of the Aβ peptide, resulting in the reduction of Ca 2+ influx into neuronal cells 7, 11. We then carried out a series of dilution experiments to find the concentration required to reduce the Ca 2+ influx by half; we obtained values of 0.1±0.02 n m and 18±3.4 n m for clusterin and Nb3, respectively (Figure 3 b,c).…”
supporting
confidence: 91%
“…We observed that both species reduced very significantly the degree of Ca 2+ influx while incubation with an anti ‐GFP antibody, as a control that does not bind to the Aβ peptide, had no detectable effect. These results are consistent with previous reports that clusterin30, 31 and Nb3 bind to oligomers of the Aβ peptide, resulting in the reduction of Ca 2+ influx into neuronal cells 7, 11. We then carried out a series of dilution experiments to find the concentration required to reduce the Ca 2+ influx by half; we obtained values of 0.1±0.02 n m and 18±3.4 n m for clusterin and Nb3, respectively (Figure 3 b,c).…”
supporting
confidence: 91%
“…Chaperones have little apparent substrate specificity and are as a rule promiscuous, recognising common features of unfolded proteins like exposed hydrophobic patches. The extracellular protein clusterin, also known as apolipoprotein J, can prevent amyloid formation by binding to prefibrillar species, and it may thus confer protection to extracellular amyloid formation [39,40]. SP-C, by design, has a high tendency to misfold and aggregate into amyloid fibrils, mediated by its polyVal domain [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have revealed that the concentration of CLU in the CSF and plasma of AD patients is significantly elevated (Sihlbom et al 2008;Thambisetty et al 2010). Interestingly, as a chaperone protein, CLU has been proven to interact with Ab peptides and this interaction plays an important role in Ab aggregation, toxicity and clearance (Baig et al 2012;DeMattos et al 2002;Narayan et al 2012;Yerbury et al 2007). Also, several studies have suggested that CLU is a potential modulator of inflammation in AD pathogenesis.…”
Section: Clusterinmentioning
confidence: 99%